Completeness of prescription information in US commercial claims databases - Lauffenburger, Julie C. (2013)
PURPOSE: Pharmacy commercial claims databases are widely used for pharmacoepidemiologic research. However, concerns have been raised that these databases may not fully capture claims for generic medication as a result of patients filling outside the context of their insurance. This has implications for many research activities and quality improvement programs. We sought to estimate the percentage of missing drug claims in US commercial claims data using a novel design. METHODS: Using a large US commercial insurance database, we examined the completeness of warfarin prescription claims among patients with atrial fibrillation receiving regular medical follow-up and testing to manage warfarin dosing. We examined 14 different 6-month cross sections. Each cross section was treated independently to identify patients with at least 2 outpatient diagnoses of atrial fibrillation, 2 international normalized ratio tests, and 1 pharmacy claim. Trends in the percentage of patients with prescription claims for generic and branded warfarin were compared by year and 6-month periods using chi-square tests and generalized linear models adjusting for patient characteristics. RESULTS: Out of 111,170 patients, the percentage of patients with any warfarin drug decreased slightly from 91.7% (95% CI: 91.0, 92.4) in early 2003 to 87.1% (95% CI: 86.7-87.6) in late 2009 (χ(2)=93.8, p<0.0001). Over the same interval, the proportion of patients with generic warfarin exposure appearing increased significantly, while the proportion of patients with branded warfarin exposure decreased significantly. CONCLUSIONS: Our study supports the possibility that some prescriptions may not be captured in US commercial insurance databases.